Complex Crystal Structure Determination and in vitro Anti–non–small Cell Lung Cancer Activity of Hsp90N Inhibitor SNX-2112 - Zhao, Dong; Xu, Yi-Ming; Cao, Lu-Qi; Yu, Feng; Zhou, Huan; Qin, Wei; Li, Hui-Jin; He, Chun-Xia; Xing, Lu; Zhou, Xin; Li, Peng-Quan; Jin, Xin; et al. (Frontiers in Cell and Developmental Biology, 2021)
SNX-2112, as a promising anticancer lead compound targeting heat shock protein 90 (Hsp90), absence of complex crystal structure of Hsp90N-SNX-2112 hindered further structural optimization and understanding on molecular interaction mechanism. Herein, a high-resolution complex crystal structure of Hsp90N-SNX-2112 was successfully determined by X-ray diffraction, resolution limit, 2.14 Å, PDB ID 6LTK, and their molecular interaction was analyzed in detail, which suggested that SNX-2112 was well accommodated in the ATP-binding pocket to disable molecular chaperone activity of Hsp90, therefore exhibiting favorable inhibiting activity on three non–small cell lung cancer (NSCLC) cell lines (IC50, 0.50 ± 0.01 μM for A549, 1.14 ± 1.11 μM for H1299, 2.36 ± 0.82 μM for H1975) by inhibited proliferation, induced cell cycle arrest, and aggravated cell apoptosis. SNX-2112 exhibited high affinity and beneficial thermodynamic changes during the binding process with its target Hsp90N confirmed by thermal shift assay (TSA, ΔTm, and −9.51 ± 1.00°C) and isothermal titration calorimetry (Kd, 14.10 ± 1.60 nM). Based on the complex crystal structure and molecular interaction analysis, 32 novel SNX-2112 derivatives were designed, and 25 new ones displayed increased binding force with the target Hsp90N verified by molecular docking evaluation. The results would provide new references and guides for anti-NSCLC new drug development based on the lead compound SNX-2112.